2018
DOI: 10.1136/annrheumdis-2018-213512
|View full text |Cite
|
Sign up to set email alerts
|

First Latin American clinical practice guidelines for the treatment of systemic lupus erythematosus: Latin American Group for the Study of Lupus (GLADEL, Grupo Latino Americano de Estudio del Lupus)–Pan-American League of Associations of Rheumatology (PANLAR)

Abstract: Systemic lupus erythematosus (SLE), a complex and heterogeneous autoimmune disease, represents a significant challenge for both diagnosis and treatment. Patients with SLE in Latin America face special problems that should be considered when therapeutic guidelines are developed. The objective of the study is to develop clinical practice guidelines for Latin American patients with lupus. Two independent teams (rheumatologists with experience in lupus management and methodologists) had an initial meeting in Panam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
91
0
12

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(111 citation statements)
references
References 49 publications
0
91
0
12
Order By: Relevance
“…1). Neither chloroquine nor hydroxychloro quine underwent conventional drug development, but their use has become a part of current treatment guide lines for rheumatoid arthritis (RA) 1 , systemic lupus eryth ematosus (SLE) [2][3][4] , antiphospholipid syndrome (APS) 5 and primary Sjögren syndrome 6,7 .…”
mentioning
confidence: 99%
“…1). Neither chloroquine nor hydroxychloro quine underwent conventional drug development, but their use has become a part of current treatment guide lines for rheumatoid arthritis (RA) 1 , systemic lupus eryth ematosus (SLE) [2][3][4] , antiphospholipid syndrome (APS) 5 and primary Sjögren syndrome 6,7 .…”
mentioning
confidence: 99%
“…РТМ широко и с большим успехом используется при СКВ в клинической практике [108] и включен в международные [109][110][111][112][113] рое вошли пациенты с активной СКВ без поражения почек, и LUNAR (Lupus Nephritis Assesment with Rituximab) [116] -с волчаночным нефритом (ВН), «первичные конечные точки», отражающие эффективность терапии, достигнуты не были (табл. 7).…”
Section: системные васкулитыunclassified
“…Recent studies have shown that this drug successfully treats patients with coronavirus pneumonia 11 . Also, the chloroquine drug has potential applications in the treatment of diseases such as rheumatoid arthritis (RA) 13 , systemic lupus erythematosus (SLE) [14][15][16] , antiphospholipid syndrome (APS) 17 and primary Sjogren syndrome 18 . Previous studies have shown that chloroquine has an antiviral mechanism and by increasing the pH, it prevents unwanted viruses such as human immunodeficiency virus (HIV) 19 , Zika virus 20,21 , Ebola virus 22 and the avian leucosis virus 23 from entering the cell.…”
Section: Introductionmentioning
confidence: 99%